THE EFFECT OF ENTREPRENEURSHIP EDUCATION ON ENTREPRENEURIAL INTENTIONS THROUGH INTERNAL LOCUS OF CONTROL AND INNOVATIVENESS: A Research on Vocational High School Students Majoring in Online Business and Marketing Expertise Program in Malang Raya - Felinda Mustika Ramadhanti Putri Islamiah; Heny Kusdiyanti; Aniek Indrawati; Farij Ibadil Maula (International Journal of Economy, Education and Entrepreneurship, 2022)
Entrepreneurial intentions are the conscious state of a person’s mind that precedes actions to start a business with a strong determination and ability to take risks by creating innovative products and services to have economic value. Therefore, entrepreneurial intentions can determine students who intend to become entrepreneurs. This research examined the effect of entrepreneurship education, internal locus of control, and innovativeness on entrepreneurial intentions. This research sample consisted of 150 students of grade XII majoring in Online Business and Marketing Expertise Programs of all Vocational High Schools in Malang Raya. The data is analyzed using descriptive statistical analysis, multiple linear regression analysis, and path analysis. This research indicated a direct effect between entrepreneurship education, internal locus of control, and innovativeness on entrepreneurial intentions. Moreover, the internal locus of control mediated entrepreneurship education on entrepreneurial intentions, while innovativeness mediated entrepreneurship education on entrepreneurial intentions